Oracle Bulk Binds技术分析 - 周晓丹; 冯少荣; 薛永生 (2007)
通过对Oracle批量绑定功能原理的分析,提出利用批量绑定技术来提高海量数据操作性能的观点;运用SQL脚本实例对比分析,验证批量绑定的强大优势,并从中研究出一种通过提高数据库缓冲区,利用分组的批量绑定方式来大幅度提高TB级数据DML性能的方法. According to the functional analysis of Oracle bulk binds,a theory which makes use of the technology of bulk binds to enhance the manipulation performance of millions of data is proposed.SQL scripts are executed to compare and establish the soundness of bulk binds,and a methodology that divides one hundred million rows' data into parts to enhance bulk binds function's performance is developed.